Study of Teachers’ Ability in Managing Science Learning in Elementary Schools in Manado City - Komedien, Brianne Eucleysia; Lumapow, Harol R.; Rawis, Joulanda A M; Kawulur, Arie (International Journal of Information Technology and Education, 2025)
This study aims to explain the relationship individually and together between creativity, professional competence, pedagogical competence, and teacher achievement motivation with teachers’ ability in managing science learning in elementary schools in Tomohon City. The research sample was Civil Servant/State Civil Apparatus teachers who were certified as professional teachers. The research method used was a survey and correlational design. Research data were collected by questionnaire and processed using simple and multiple correlation analysis techniques. The results of the study include teacher creativity having a positive and significant relationship with teachers’ ability in managing science learning; teacher professional competence is positively and significantly related to teacher ability in managing science learning; teacher pedagogical competence is positively and significantly related to teacher ability in managing science learning; teacher achievement motivation is positively and significantly related to teacher ability in managing science learning; and creativity, professional competence, pedagogical competence, and teacher achievement motivation are positively and significantly related simultaneously to teacher ability in managing science learning. After discussing the research results, it was continued by drawing research conclusions and putting forward suggestions, including that this research can be developed by other researchers to test variables that function as mediator and moderator variables using the structural equation model (SEM).